Go International's Strategy On East Java Handicraft MSMES: A Case Study In The Creative Industry - Afif Nur Rokhman; Sudarmiatin; Heri Pratikto (Abadi Institute, 2026)
This study aims to analyze the strategy of going international in Micro, Small, and Medium Enterprises (MSMEs) in the handicraft sector in East Java with a case study approach on Written Batik MSMEs